Butterfly as bioindicator for development of conservation areas in Bukit Reban Kambing, Bukit Belading and Bukit Tukau, Johor, Malaysia - NORRADIHAH ISMAIL; Aqilah Awg Abdul Rahman; Maryati Mohamed; Mohd Fadzelly Abu Bakar; Lili Tokiman (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ismail N, Rahman A A A, Mohamed M, Abu Bakar M F, Tokiman L. 2020. Butterfly as bioindicator for development of conservation areas in Bukit Reban Kambing, Bukit Belading and Bukit Tukau, Johor, Malaysia. Biodiversitas 21: 334-344. Butterflies are often used as indicator surrogates to evaluate the quality of ecosystems. This is made possible due to their sensitive responses toward environmental fluctuations and habitat changes. Butterflies were collected opportunistically using aerial nets at three hill dipterocarp forests; Bukit Reban Kambing (BRK), Bukit Belading (BB) and Bukit Tukau (BT) of Johor, Malaysia from 8th to 11th March 2016. The objectives of this study are to provide a checklist of butterflies of the hills and evaluate habitat suitability in an effort to support the proposal to gazette the hills as part of the Gunung Ledang protected area. A total of 60 individuals belonging to 23 species, 21 genera, and five families were recorded. Comparing the three hills, BRK recorded the greatest individual and species numbers, followed by BT and BB. BRK recorded the highest Shannon diversity index, H’ (2.272) value, whereas BB presented the highest value of species evenness index, E’ (0.945). MaxEnt modeling of the butterflies in BRK, BB, and BT showed a network of high habitat suitability areas connecting Gunung Ledang and our sampling locations. Despite limited sampling effort, this baseline data could possibly strengthen the effort for gazettement and prevent further pressure from mining activity and land conversion.